2014
DOI: 10.1111/are.12421
|View full text |Cite
|
Sign up to set email alerts
|

Molt-inhibiting hormone (MIH) gene from the green mud crabScylla paramamosainand its expression during the molting and ovarian cycle

Abstract: Mud crab is a group of commercially important species that are found throughout the Indo-Pacific region. In this study, the full-length cDNA of molt-inhibiting hormone (Scp-MIH) was cloned from the green mud crab, Scylla paramamosain. The conceptually translated peptide precursor consists of a 78-residue mature peptide, preceded by a 35-residue signal peptide. The mature peptide shares a high identity with the other known MIHs, and contains six conserved cysteine residues that have been proposed to be function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…At temperatures that juvenile M. magister tolerate over prolonged periods (10 and 15°C; Kondzela and Shirley, 1993), Mm-MIH was constitutively expressed over the moult cycle, as expected. A decrease of MIH expression in premoult was reported for Callinectes sapidus and in Scylla paramamosain (Huang et al, 2015;Lee et al, 1998) and observed in our experimental animals at 20°C. Transcription was downregulated at 20°C also in the other genes, but to a lesser extent.…”
Section: Discussionsupporting
confidence: 85%
“…At temperatures that juvenile M. magister tolerate over prolonged periods (10 and 15°C; Kondzela and Shirley, 1993), Mm-MIH was constitutively expressed over the moult cycle, as expected. A decrease of MIH expression in premoult was reported for Callinectes sapidus and in Scylla paramamosain (Huang et al, 2015;Lee et al, 1998) and observed in our experimental animals at 20°C. Transcription was downregulated at 20°C also in the other genes, but to a lesser extent.…”
Section: Discussionsupporting
confidence: 85%
“…During the ovarian development of S. paramamosain , the expression levels of Sp‐CHH increased significantly from stage I to stage IV, when the ovary develops from an undeveloped stage and go through stages of active vitellogenesis and oocyte maturation, and declined at stage V, when vitellogenesis has completed (Huang Ye, et al . ). These results strongly suggested that Sp‐CHH might be concerned with vitellogenesis in the mud crab.…”
Section: Discussionmentioning
confidence: 97%
“…A β ‐actin fragment was amplified using the primer pair, Actinf and Actinr (Table ), and served as the internal control (Huang, Ye, et al . ). The PCR conditions were as follows: an initial denaturation (1 min, 95°C), 45 cycles of denaturation (30 s, 95°C), annealing (30 s, 55°C), and extension (40 s, 72°C).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…NPF and NPY belong to NPY family are neuropeptide hormone that accelerates ovarian maturation in female Schistocerca gregaria (SCHOOFS et al 2001), and plays a role in the regulation of visceromotor functions during egg laying (RAJPARA et al 1992). CHH , MIH have long been considered to inhibit crustacean molting, and after E. sinensis finish their last reproductive molting like insects, they will stop molting and initiate their gonad development (CHAN et al 2003; HUIYANG et al 2015). Therefore, extremely highly expressed CHH , MIH in eyestalk may inhibit the molting and induce precocity.…”
Section: Discussionmentioning
confidence: 99%